Hospital workers’ pro-environmental behavior: a qualitative interview study - Rasdi, Irniza; Shen, Tao; Ezani, Nor Eliani; San, Ong Tze (Human Resources Management Academic Research Society (HRMARS), 2024)
In today’s world, there is increasing recognition of the severity of environmental issues that can be addressed via the adoption of more pro-environmental behavior among people. Hospital workers, the guardians of human health, must be fully aware of the negative effects resulted from urgent environmental issues. However, it is unclear that the perception of proenvironmental behavior among hospital workers. To this end, we undertook a qualitative study via in-depth interviews to represent different thoughts of pro-environmental behavior. Four themes, opinion on pro-environmental behavior, level of pro-environmental behavior, hindering factors, and driving factors, were identified. The level of pro-environmental behavior was uneven, some workers had high pro-environmental behavior, while some were insufficient or even missing. Moreover, hindering factors and driving factors of hospital workers’ pro environmental behavior were different from the general public to some extent, specifically, the responsibility of work, standards and regulations in the medical field, organizational barriers, and physical mental feeling were the primary hindering factors, and demographic characteristics, psychological variables, and organizational facilitators were important driving factors of pro-environmental behavior among hospital workers. Further research should quantify the promotion of pro-environmental behavior by certain factors and identify effective intervention measures to alleviate environmental issues.